Toward a common understanding: supporting and promoting education scholarship for medical school faculty. Issue 12 (December 2014) - Van Melle, Elaine; Lockyer, Jocelyn; Curran, Vernon; Lieff, Susan; St Onge, Christina; Goldszmidt, Mark
<x xml:space="preserve">Abstract</x> Context Education scholarship (ES) is integral to the transformation of medical education. Faculty members who engage in ES need encouragement and recognition of this work. Beginning with the definition of ES as 'an umbrella term which can encompass both research and innovation in health professions education', and which as such represents an activity that is separate and distinct from teaching and leadership, the purpose of our study was to explore how promotion policies and processes are used in Canadian medical schools to support and promote ES. Methods We conducted an analysis of the promotion policies of 17 Canadian medical schools and interviews with a key informant at each institution. We drew on an interpretive approach to policy analysis to analyse the data and to understand explicit messages about how ES was represented and supported. Results Of the 17 schools' promotion documents, only nine contained specific reference to ES. There was wide variation in focus and level of detail. All key informants indicated that ES is recognised and considered for academic promotion. Barriers to the support and recognition of ES included a lack of understanding of ES and its relationship to teaching and leadership. This was manifest in the variability in promotion policies and processes, support systems, and career planning and pathways for ES. Conclusions This lack of clarity may make it challenging for medical school faculty members to make sense of how they might successfully align ES within an academic career. There is a need therefore to better articulate ES in promotion policies and support systems. Creating a common understanding of ES, developing guidelines to assess the impact of all forms of ES, developing an informed leadership and system of mentors, and creating explicit role descriptions and guidelines are identified as potential strategies to ensure that ES is appropriately valued.